Konstruksi Sosok Ibu Disabilitas Netra dalam Iklan Dancow Fortigro di Youtube - Putri, Fathia Aqila Zahra; Delliana, Santi (UNIVERSITAS KALBIS, 2025)
The mother figure is a very important figure and also has a big role in the family. In the Dancow Fortigro advertisement entitled “My mother is different, but #LoveBundaSempurna” the figure of a mother with a visual disability appears predominately. This study aims to determine the construction of the figure of a mother with visual disabilities who appears in Dancow Fortigro's advertisement entitled